2008
DOI: 10.1111/j.1582-4934.2008.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells expressing TRAIL lead to tumour growth inhibition in an experimental lung cancer model

Abstract: Lung cancer is a major public health problem in the western world, and gene therapy strategies to tackle this disease systemically are often impaired by inefficient delivery of the vector to the tumour tissue. Some of the main factors inhibiting systemic delivery are found in the blood stream in the form of red and white blood cells (WBCs) and serum components. Mesenchymal stem cells (MSCs) have been shown to home to tumour sites and could potentially act as a shield and vehicle for a tumouricidal gene therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 43 publications
3
87
1
3
Order By: Relevance
“…Contrary to previously said, MSCs (similar to most other healthy cells) are unsusceptible to TRAIL-induced apoptosis [71]. In addition to this, in the TRAIL transfected adult MSCs, fetal-MSCs and umbilical cord matrix stem cells, there are almost undetectable levels of apoptotic pathway components (caspase-8 and caspase-9) [110].…”
Section: Us20150086515 (2015)contrasting
confidence: 39%
See 2 more Smart Citations
“…Contrary to previously said, MSCs (similar to most other healthy cells) are unsusceptible to TRAIL-induced apoptosis [71]. In addition to this, in the TRAIL transfected adult MSCs, fetal-MSCs and umbilical cord matrix stem cells, there are almost undetectable levels of apoptotic pathway components (caspase-8 and caspase-9) [110].…”
Section: Us20150086515 (2015)contrasting
confidence: 39%
“…In experiments with MSCs expressing tumor necrosis factor-related apoptosis inducing ligand (TRAIL) (a type II membrane ligand from Tumor Necrosis Factor (TNF) family) anticancer effects are also detected, probably by induction of apoptosis [68][69][70][71][72][73][74]. This effect was reported in case of prostate cancer investigated [19], and also in other experimental cancer models (glioma and lung cancer).…”
Section: Mscs Engineered As Anticancer Drug De-livery Systemsmentioning
confidence: 59%
See 1 more Smart Citation
“…Most of previous published studies used the serotype 5 adenoviral vector (Ad5) as a delivery vector to deliver hTRAIL into the targeted cells [29][30][31][32][33][34][35] although other vector systems were also used, such as AAV. 36 Some studies used the E1 deleted Ad5 vector, which vector could not replicate in the targeted cells.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also shown the antiproliferative, antitumor and immunomodulatory effects of interferon-a, 27 a multifunctional regulatory cytokine. Mohr et al 28 reported the ability of an adenoviral vector expressing tumor necrosis factor-related apoptosis-inducing ligand to transduce MSCs and the subsequent therapeutic efficacy of these MSCs in a lung cancer model. The potential of mesenchymal progenitor cells to assist the delivery of an oncolytic virus, which targets virus-mediated lysis of tumor cells has been evaluated and may be a novel approach for human glioma therapy.…”
Section: Glioma Tropism Of Mscmentioning
confidence: 99%